Zika Virus Alters the Viscosity and Cytokines Profile in Human Colostrum - Ocilma B. de Quental; Eduardo L. França; Adenilda C. Honório-França; Tassiane C. Morais; Blanca E. G. Daboin; Italla M. P. Bezerra; Shirley V. Komninakis; Luiz C. de Abreu (Journal of Immunology Research)
The resurgence of cases of Zika virus (ZIKV) infection, accompanied by epidemic of microcephaly in Brazil, has aroused worldwide interest in understanding the biological mechanisms of the virus that allow patient management and the viral dissemination control. Colostrum and human milk are possible sources of virus spread. Therefore, the objective of this study was to analyze the repercussions of ZIKV infection on rheological parameters and inflammatory cytokines of colostrum. The prospective cohort study included 40 puerperal donors of colostrum, divided into 2 groups: control (without ZIKV infection, n=20) and a group infected with ZIKV during the gestational period (n=20). Analyses were performed for the detection of ZIKV by polymerase chain reaction (PCR). In addition to obtaining the rheological parameters and quantification of IL-10 and IL-6 cytokines by flow cytometry, ZIKV and other flaviviruses were not detected in colostrum. However, maternal infection reflected increased viscosity, decreased levels of IL-10, and elevated levels of IL-6. The higher viscosity may represent a mechanical barrier that hinders the spread of the virus. The lower levels of anti-inflammatory mediators and higher inflammatory cytokines may possibly alter the viscosity, and it seems the higher viscosity represents a possible mechanism of adaptation of breastfeeding against a response to ZIKV.